Pendampingan Pembuatan Desain Card Sorting Game Pada Topik Aljabar Di MGMP Matematika SMP/MTS Wilayah Koordinator Jatinom Klaten - Aryuna, Dyah Ratri; Sujatmiko, Ponco; Pramudya, Ikrar; Mardiyana, Mardiyana; Setiawan, Rubono; Nasution, Nur Baiti (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Teachers of MGMP Mathematics SMP/MTs Jatinom Coordinator Area of Klaten have found that many students still fail to complete tasks on algebra material correctly. This clearly shows that students are struggling to learn algebra. On the other hand, we must address the issue of learning mathematics in a play situation, which has become a concern of late. Games are an effective tool for helping students learn and encouraging their participation in an engaging, interactive learning environment. This community service activity will assist teachers in MGMP Mathematics SMP/MTs Jatinom Coordinator Area Klaten in making Card Sorting Games on the topic of algebra. After participating in this activity, teachers will be able to develop learning algebra material in a play situation with the help of card media. Teachers will work in groups to create a Card Sorting Game design on the topic of algebra. They will do this both online and offline. The response of the teachers was positive. They were active participants during the activity.